An evaluation of the use of machine translation among Arab students / Talal Mohammad Ahmad Barghouthi - Ahmad Barghouthi, Talal Mohammad (2012)
The last thirty years, the internet has come to govern our lives and has emerged as one of the main means of communication. Translation is one of the areas which has been greatly affected by the rapid progress in online communication. Research and development undertakings for machine translation systems focus more on the translation of English language to other languages more than other languages, dependence on these systems. Problems arise when Arab students in the Faculty of Islamic studies, University of Malaya, who conduct their researches in Arabic are required to furnish an English version of their abstract. Since they rely on free on-line translation, translation flaws have led to a lot of misunderstanding when their supervisors read the English version of their abstracts. With that in mind, this study will look at the perception of users towards machine translation, mainly free online translation by using Google translate engine. This study employed the “Black-box” methodology to evaluate the quality of machine translation products (Hutchins and Somers, 1992). In the black-box evaluation, the evaluator has to look at the system’s input and output. Therefore, samples of students’ abstracts translated by the free on-line translation tools are evaluated for accuracy. The design of this study relies on a questionnaire and interviews to obtain information on the users’ perception on the use of machine translation tools. This study concluded that free on-line translation tools, specifically the Google translation engine is not considered a reliable system which can produce accurate and acceptable Arabic- English translation output.